Importance of Reference Muscle Selection in Quantitative Signal Intensity Analysis of T2-Weighted Images of Myocardial Edema Using a T2 Ratio Method. (21st June 2015) - Carbone, Iacopo; Childs, Helene; Aljizeeri, Ahmed; Merchant, Naeem; Friedrich, Matthias G.
Abstract : Objectives. The purpose of our study was to identify the suitability of various skeletal muscles as reference regions for calculating the T2 SI ratio for a semiautomated quantification of the extent of myocardial edema with T2-weighted images. Methods . Thirty-four patients with acute myocardial infarction (MI) were enrolled. The extent of myocardial edema was determined by T2 SI ratio map, using 4 different muscles as reference: major and minor pectoralis, serratus anterior, teres minor-infraspinatus, and subscapularis. The size of myocardial edema as visually quantified was used as the standard of truth. The control group consisted of 15 patients with chronic MI. Intra- and interobserver variability were assessed. Results . Due to poor image quality four patients were excluded from the analysis. In acute MI patients, serratus anterior muscle showed the strongest correlation with the visual analysis (r = 0.799 ;P < 0.001 ) and low inter- and intraobserver variability, while the other muscles resulted in a significant interobserver variability. In contrast, the use of other muscles as a reference led to overestimating edema size. Conclusions . In acute MI patients, serratus anterior resulted to be the most reliable and reproducible muscle for measuring the extent of myocardial edema.